Rho 구아닌 뉴클레오타이드 교환 인자 12[Rho Guanine Nucleotide Exchange Factor 12, ARHGEF12] 억제제를 이용한 녹내장 치료 - PRAVEEN KAVITA; SCHURMANN CLAUDIA; BARAS ARIS; GURSKI LAUREN; FERREIRA MANUEL ALLEN REVEZ; COPPOLA GIOVANNI (2024)
본 개시는 녹내장 또는 안압[intraocular pressure, IOP] 상승을 겪는 대상을 치료하는 방법, 녹내장 발생 또는 IOP 발생 위험이 증가된 대상을 식별하는 방법, 인간 Rho 구아닌 뉴클레오타이드 교환 인자 12[Rho Guanine Nucleotide Exchange Factor 12, ARHGEF12] 변이체 핵산 분자 및 변이체 폴리펩타이드를 검출하는 방법, 및 ARHGEF12 변이체 핵산 분자 및 변이체 폴리펩타이드를 제공한다. The present disclosure provides methods of treating subjects having glaucoma or elevated intraocular pressure (IOP), methods of identifying subjects having an increased risk of developing glaucoma or developing elevated IOP, methods of detecting human Rho Guanine Nucleotide Exchange Factor 12 (ARHGEF12) variant nucleic acid molecules and variant polypeptides, and ARHGEF12 variant nucleic acid molecules and variant polypeptides.